Charles S. Peirce: uma chave de leitura do constructo imaterialista de George Berkeley - Melo, Caique Marra de (2019)
The dissertation aims to present George Berkeley’s immaterialist construct based on a series of notes by Charles S. Peirce, mostly present in his review of The Works of George Berkeley by Alexander C. Fraser, published in 1871. For this, the dissertation is composed of three main fronts: (1) elements from the thoughts of William of Ockham and Thomas Hobbes who, influencing George Berkeley, strengthen Peirce's thesis about unity, if you prefer, continuity, present in the medieval-modern transition in the history of British philosophy; (2) the interpretative polemic about John Locke's theory of abstraction and the consequent Berkeleyan opportunism, which makes it possible to deduce the idealism of the bishop of Cloyne; and (3) the construction of Berkeley’s immaterialist edification, which presents itself as an alternative in order to overcome the problem of the unknowability of the world, generated, according to the bishop, by a kind of “materialist abstractionism”. The present investigation, therefore, given the exercises of localization and scrutiny of the epistemological and methodological assumptions of Berkeley in the midst of the linearity of British thought, as well as their respective applications throughout the argumentative stages of the development of his immaterialist philosophy, finds its criterion of justification as the exposition of the truth doctrine of Berkeley proves to be an essential key to the reading of the movement of modern philosophy, especially British, as a whole, since, in addition to strengthening the thesis about the unity present in the medieval-modern link in the philosophy of the British Isles, it contributes to pointing to the tortuous north towards which a nominalism carried to its ultimate consequences would guide, emphasizing Berkeley's thinking in its position of inevitable “resting place” between John Locke and David Hume. In addition, as a mere addendum to a precedent opening for future investigations, the dissertation brings, in its Final considerations, an introductory reflection regarding the analysis of proto-pragmatic traits in George Berkeley's thought, being such an investigation attentive to Berkeley's refinement concerning the definitions of things limited to the totality of their immediate practical effects and to the possible pragmatic character present in his understanding of the applicability of scientific theories